The Gut Microbiota and Inflammatory Factors in Pediatric Appendicitis. (7th July 2022) - Bi, Yuewei; Yang, Qianyu; Li, Jiao; Zhao, Xufeng; Yan, Beilei; Li, Xuan; Cui, Hualei
Abstract : Background . The study analyzed gut microflora's composition and investigated the associations between the associations between gut dysbiosis and inflammatory indicators in pediatric patients with acute appendicitis. Methods . High-throughput sequencing and bioinformatics analysis were used to investigate the composition and diversity of gut microflora in 20 pediatric patients with acute appendicitis and 11 healthy children. Endpoints measured were operational taxonomic units (OTU) of gut microflora. The OTU and its abundance analysis, sample diversity analysis, principal component analysis of samples, differential analysis, and analysis of biomarkers were performed. Results . Overall fecal microbial richness and diversity were similar in patients and controls. Yet richness within the group of Bilophila, Eggerthella, Clostridium, Parvimonas, Megasphaera, Atopobium, Phascolarctobacterium, Adlercreutzia, Barnesiella, Klebsiella, Enterococcus, and Prevotella genera was higher in patients. Adlercreutzia was significantly positively correlated with IL-10, while the three other genera, comprising Klebsiella, Adlercreutzia, and Prevotella, were positively correlated with B cells level. Conclusion . Gut microbiome components are significantly different in pediatric patients with acute appendicitis and healthy children. The differential abundance of some genera is correlated with the production of inflammatory markers in appendicitis.